Importance of Rose Bengal Loaded with Nanoparticles for Anti-Cancer Photodynamic Therapy - Batoul Dhaini; Laurène Wagner; Morgane Moinard; Joël Daouk; Philippe Arnoux; Hervé Schohn; Perrine Schneller; Samir Acherar; Tayssir Hamieh; Céline Frochot (MDPI AG, 2022)
Rose Bengal (RB) is a photosensitizer (PS) used in anti-cancer and anti-bacterial photodynamic therapy (PDT). The specific excitation of this PS allows the production of singlet oxygen and oxygen reactive species that kill bacteria and tumor cells. In this review, we summarize the history of the use of RB as a PS coupled by chemical or physical means to nanoparticles (NPs). The studies are divided into PDT and PDT excited by X-rays (X-PDT), and subdivided on the basis of NP type. On the basis of the papers examined, it can be noted that RB used as a PS shows remarkable cytotoxicity under the effect of light, and RB loaded onto NPs is an excellent candidate for nanomedical applications in PDT and X-PDT.